2012
DOI: 10.1111/1471-0528.12015
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of HPV infection over time in European women who are HIV‐1 positive

Abstract: Objective The objectives of the study were to investigate high-risk human papillomavirus (HR-HPV) infection and type distribution in women infected with HIV-1, and to determine the relevance of HR-HPV positivity and persistence/loss to the development of high-grade cervical disease.Design A total of 518 European women infected with HIV attending for routine gynaecological care consented to 6-monthly follow-up visits over 3 years, with surveillance of cytology, colposcopy and histopathology, where relevant, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 24 publications
5
31
1
Order By: Relevance
“…Compared with the above, a multicentre Catalan study revealed inadequate rates of cervical cancer screening with only 50% of HIV positive women reporting that they had annual screening [15]. It is worth mentioning that in a prospective study of HPV infection among HIV positive women from European countries with a study population of over IDU -injected drug users; CI -confidence interval; OR -odds ratio 1100 women, only 55.5% provided a second sample after 6 or more months [3]. In our study of women receiving routine care, over half the women had two or more cytological tests performed, which is still an unsatisfactory result.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Compared with the above, a multicentre Catalan study revealed inadequate rates of cervical cancer screening with only 50% of HIV positive women reporting that they had annual screening [15]. It is worth mentioning that in a prospective study of HPV infection among HIV positive women from European countries with a study population of over IDU -injected drug users; CI -confidence interval; OR -odds ratio 1100 women, only 55.5% provided a second sample after 6 or more months [3]. In our study of women receiving routine care, over half the women had two or more cytological tests performed, which is still an unsatisfactory result.…”
Section: Discussionmentioning
confidence: 94%
“…HIV-positive women are at increased risk of acquiring HPV and of the HPV infection and persistency of HPV infection, especially with high-risk HPV [2,3]. As a consequence, this group of women presents a five to six times higher risk of cervical cancer [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we chose to match WLWH and WGP on age and prior cytology/histology results. The overall hrHPV prevalence in WLWH of 26.4 % was lower than the hrHPV prevalence found in the European MACH-1 collaborative group of WLWH with a prevalence close to 50 % [15], however participants in the MACH study were younger (median age: 35 versus 42.5 years), less likely to be on HAART (69.7 % versus 94.9 %) and a different assay (Hybrid Capture II) was used for HPV detection. On a global scale the highest prevalence of HPV in WGP with normal cytological findings is found in Africa (24 %) [14].…”
Section: Discussionmentioning
confidence: 96%
“…The hrHPV genotype distribution in Denmark [11, 12] and worldwide is well described in WGP and globally HPV16, 18, 52, 31, and 58 predominate [10, 13, 14]. Most studies suggest a different HPV genotype distribution in WLWH with increased frequency of non-16/18 HPV genotypes, which are not targeted by the 2-and 4-valent HPV vaccines [8, 15, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…Men and women with HIV infection show an increased risk and rate of HPV acquisition and persistence, frequent carriage of multiple HPV types, and an increased risk of HPV‐related disease including rapidly progressive malignancies . HPV carriage rates and overall disease risk increase at low CD4 cell counts.…”
Section: Human Papilloma Virusmentioning
confidence: 99%